SpatialData: an open and universal data framework for spatial omics - Marconato, Luca; Palla, Giovanni; Yamauchi, Kevin A.; Virshup, Isaac; Heidari, Elyas; Treis, Tim; Vierdag, Wouter-Michiel; Toth, Marcella; Stockhaus, Sonja; Shrestha, Rahul B.; Rombaut, Benjamin; Pollaris, Lotte; et al. (Nature methods, 2024)
Spatially resolved omics technologies are transforming our understanding of biological tissues. However, the handling of uni- and multimodal spatial omics datasets remains a challenge owing to large data volumes, heterogeneity of data types and the lack of flexible, spatially aware data structures. Here we introduce SpatialData, a framework that establishes a unified and extensible multiplatform file-format, lazy representation of larger-than-memory data, transformations and alignment to common coordinate systems. SpatialData facilitates spatial annotations and cross-modal aggregation and analysis, the utility of which is illustrated in the context of multiple vignettes, including integrative analysis on a multimodal Xenium and Visium breast cancer study.
Gesehen am 23.08.2024